2014
DOI: 10.1177/1071100714540886
|View full text |Cite
|
Sign up to set email alerts
|

An Anatomical Study Comparing Two Surgical Approaches for Isolated Talonavicular Arthrodesis

Abstract: These data support for the use of the dorsal approach for talonavicular arthrodesis, particularly in cases where access to the lateral half of the joint is necessary.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…They used a dorsal approach to prepare the TNJ, while we used a medial approach. An anatomical study showed that the total accessible talonavicular articular surface area for the medial and dorsal approaches was 71% and 92%, respectively [ 37 ]. Another study showed that 91% of the TNJ and STJ areas could be accessed through the medial approach [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They used a dorsal approach to prepare the TNJ, while we used a medial approach. An anatomical study showed that the total accessible talonavicular articular surface area for the medial and dorsal approaches was 71% and 92%, respectively [ 37 ]. Another study showed that 91% of the TNJ and STJ areas could be accessed through the medial approach [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…Another study showed that 91% of the TNJ and STJ areas could be accessed through the medial approach [ 38 ]. It is important to note that all the anatomical specimens in both studies had no deformity [ 37 , 38 ]. In advanced AAFD, the hindfoot is in valgus, and the forefoot is abducted, allowing even superior access to these joints in comparison to normal feet when a medial approach is used [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Because of the concave-convex nature of the joint, a medial percutaneous approach has been advocated as preferred for ease of access. 5 However, some studies have found the dorsal approach to be more suitable for more adequately preparing the joint surface, an essential process for subsequent fusion. 1,15 Percutaneous approaches carry the potential advantages of causing decreased tissue trauma, incision size, surgical site inflammation, and less pain.…”
Section: Introductionmentioning
confidence: 99%
“…6 Alternative percutaneous methods have been suggested for talonavicular fusion. 1,5,6,12,18 Although there are benefits to an arthroscopic approach, it may take a longer time to set up an operating room, and instruments may not be available in all facilities.…”
Section: Introductionmentioning
confidence: 99%
“…The talonavicular (TN) joint is a multiaxial, ball-and-socket joint that functions as the cornerstone of the medial joint complex of the hindfoot, allowing for controlled movements 20 and distributing forces among the peritalar joints during the gait cycle. 1,8,12,13,17 The TN joint can be associated with an array of musculoskeletal pathologies, including joint degeneration, inflammatory processes, and traumas. 2,5,17,21 TN fusion is a reliable intervention for degenerative, inflammatory, and traumatic TN joint pathology as well as many hindfoot deformities.…”
mentioning
confidence: 99%